The Significance of Buffer Solutions on Corrosion Processes of Cobalt Ferrite CoFe2O4 Thin Film on Different Substrates - Elsayed, Elsayed M.; Khalil, Hazem F.; Ibrahim, Ibrahim A.; Hussein, Mostafa R.; El-Sabbah, Mohamed M.B. (Combinatorial Chemistry & High Throughput Screening, 2020)
Background: The spinel ferrite nanoparticles, such as zinc, nickel, and cobalt ferrites have exceptional electronic and magnetic properties. Cobalt ferrite nanomaterial (CoFe2O4) is a hard material that reveals high magnetic, mechanical, and chemical stability. Aim and Objective: The objective of this research is to predict the corrosion behavior of cobalt ferrite (CoFe2O4) thin films deposited on different substrates (platinum Pt, stainless steel S.S, and copper Cu) in acidic, neutral, and alkaline medium. Materials and Methods: Cobalt ferrite thin films were deposited on platinum, stainless steel, and copper via electrodeposition-anodization process. After that, corrosion resistance of the prepared nanocrystalline cobalt ferrite on different substrates was investigated in acidic, neutral, and alkaline medium using open circuit potential and potentiodynamic polarization measurements. The crystal structure, crystallite size, microstructure, and magnetic properties of the ferrite films were investigated using a combination of XRD, SEM and VSM. Results: The results of XRD revealed a cubic spinel for the prepared cobalt ferrite CoFe2O4. The average size of crystallites was found to be about 43, 77, and 102 nm precipitated on platinum, stainless steel, and copper respectively. The magnetic properties of which were enhanced by rising the temperature. The sample annealed at 800oC is suitable for practical application as it showed high magnetization saturation and low coercivity. The corrosion resistance of these films depends on the pH of the medium as well as the presence of oxidizing agent. Conclusion: Depending on the obtained corrosion rate, we can recommend that, CoFe2O4 thin film can be used safely in aqueous media in neutral and alkaline atmospheres for Pt and Cu substrates, but it can be used in all pH values for S.S. substrate.
Keywords: cobalt ferrites